BAHASA KEBANGSAAN DALAM LINGKUP PERGAULAN BANGSA-BANGSA - Dewi, Mutiara Indah Nirmala (JURNAL KEBANGSAAN RI, 2024)
Dynamic languages ​​follow a cycle that continues to develop. In the process, assimilation occurs which involves various language elements originating from local or foreign absorption in every language in the world. Including Indonesian, sometimes in its use it is assimilated with terms taken from foreign languages. This especially appears in informal spaces. Elements of foreign absorption, both from English and other foreign languages, color the course of people’s language behavior. Another space that provides flexibility for seeding foreign absorption is in the media. Therefore, in this regard, the research aims to determine the process of absorption of local languages ​​into national languages. Meanwhile, the approach used is qualitative with a documentation study method. The research results show that the element of local absorption occurs because of the large number of media users in the wider community presented in the digital world. Absorption of foreign language elements is considered to improve social status because it can be interpreted as progress.